Constructing an Art Museum of the Future through the Experience of a “Future Spectator”: A Thought Experiment after Pierre Huyghe’s “I L YA” Exhibition - Burkhanova, Aleksandra B. (Actual Problems of Theory and History of Art, 2017)
The article presents a philosophical perspective on the Art Museum of the Future — after the end of a work of art as a unitary object created by an individual artist. The concept of “the future” incorporates the concept of art as an event that “happens” to a human-being — not a professional choice, genius, or skill. Art happens repetitively, on multiple occasions, although each time in a surprising fashion. The linear paradigm of time is therefore replaced with the notion of time as a spiral: “the future” appears as a return of forgotten sensations caused by the suspicious familiarity of new-coming things. In this speculative realm where everything can be art, the profound question is posed to a spectator’s experience of the Art Museum of the Future. Inspired by the concept of “future people” by neuro-philosopher Paul Churchland, the “future spectator” by Burkhanova constitutes a thought experiment of walking through the imaginary space of the Future Museum, not asking: “What is Art?” — But instead: “What may it become, and what are the conditions of its becoming?” In conclusion, the end of the work of art constitutes not only the end of fundamental criteria that allow aesthetic judgement and separation between form and content, the signifier and the signified. The Art Museum of the Future materializes as a “place of potency” where things and events are released from any contextualization. In their becoming, the artworks fulfil their multiple potentials in unexpected ways and synchronize with their spectator.